The cytosolic invertase NI6 affects vegetative growth, flowering, fruit set, and yield in tomato - Coluccio Leskow, Carla (2021)
Sucrose metabolism is important for most plants, both as the main source of carbon and via signaling mechanisms that have been proposed for this molecule. A cleaving enzyme, invertase (INV) channels sucrose into sink metabolism. Although acid soluble and insoluble invertases have been largely investigated, studies on the role of neutral invertases (A/N-INV) have lagged behind. Here, we identified a tomato A/N-INV encoding gene (NI6) co-localizing with a previously reported quantitative trait locus (QTL) largely affecting primary carbon metabolism in tomato. Of the eight A/N-INV genes identified in the tomato genome, NI6 mRNA is present in all organs, but its expression was higher in sink tissues (mainly roots and fruits). A NI6-GFP fusion protein localized to the cytosol of mesophyll cells. Tomato NI6-silenced plants showed impaired growth phenotype, delayed flowering and a dramatic reduction in fruit set. Global gene expression and metabolite profile analyses of these plants revealed that NI6 is not only essential for sugar metabolism, but also plays a signaling role in stress adaptation. We also identified major hubs, whose expression patterns were greatly affected by NI6 silencing; these hubs were within the signaling cascade that coordinates carbohydrate metabolism with growth and development in tomato.